Dampak Krisis Global terhadap Non Performing Loan Bank Devisa Nasional - Suharyono Suharyono; Nazrantika Sunarto (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2016)
The global crisis has resulted non performing loan (NPL) increased. The measurement of the banks non performing loan ratio is applicable to assess the composite rating of a bank, as the impact of the global crisis toward non performing loan of foreign exchange banks. This study aimed to determine whether there was significant difference between foreign exchange banks non-performing loan before and after the global crisis. The Bank’s non performing loans was measured by comparing the Non-Performing Loan to the total credit. The population of this study was 35 foreign exchange banks. The Hypothesis was tested by using Mann Whitney different test and Independent Sample T Test. The research of this study showed that non performing loan of foreign exchange banks before, during, and after global crisis did not have significant difference.